Public perceptions of non-native plant species on a Chilean sub-Antarctic island - Crete, Gaelle; Herrmann, Thora Martina; Fortin, Cloe; Schuttler, Elke (My University, 2020)
Humans are the main drivers of the introduction, establishment and spread of non-native species worldwide but they have traditionally been excluded from management. Nowadays, the social component of non-native species is increasingly considered. In this paper, we investigated understanding, perceptions and attitudes towards management of non-native herbaceous plant species on Navarino, a remote Chilean sub-Antarctic island. Overall, our study showed a general understanding of the non-native species concept among the interviewees but revealed a lack of consciousness regarding non-native plants species in the local context. Interestingly, our study also revealed many positive values associated with non-native plants species on Navarino, particularly the esthetic value. Whilst some non-native plants were strictly associated with positive values, such as common daisy (Bellis perennis) and white clover (Trifolium repens), most species were associated with conflicting values. As a key result, our study lastly showed that most interviewees were indifferent about the management of the non-native herbaceous plant species. We, therefore, suggest (i) increasing the awareness of stakeholders with respect to non-native plants, (ii) incorporating stakeholder's values into future management decisions and (iii) considering the strategic location of Navarino Island as a potential stepping stone for the dispersion of non-native plants species towards the Antarctic.
Keywords: biological invasions; co-management; community; protected areas; subpolar regions; values